A Review on Green Building Index: Management Criteria (Sains Humanika, 2016)
This paper reviews â€œmanagementâ€ criteria in green building standard worldwide. There are several issues related to the â€œmanagementâ€ criteria of green building that include the increase of property management and maintenance costs, the occurrence of incompatible maintenance programs, underutilization of property, end-user dissatisfaction, role of manager; lack of knowledge, skill and experience; and lack of proper financial planning. Twenty-seven green building indexes are reviewed. Summary of â€œmanagementâ€ criteria are presented from six green building standards. Current study has been proposed a set of â€œmanagement criteriaâ€.
Keywords: Green building index; management criteria